Open Science challenges for information literacy - Lopes, Carlos (2018)
This chapter intends to explore the integration of Open Science concepts in Information Literacy. It presents a theoretical reflection that shows the contributions of Information Literacy and the 2016 Framework for Information Literacy for Higher Education in the academic context and in the dynamics of science production. The scope of Open Science translates into a collaborative, transparent process of dissemination, creation, and transfer of knowledge, accessible to research and based on the Open Access principles. The different agents of the research process provided with a set of Information Literacy skills, in print or digital information environments, and based on their own critical and reflexive thinking, acquire the ability to transform information into new knowledge. Information Literacy is concluded to be an essential learning tool for the development of Open Science, guided by the new ACRL Framework, enhancing the critical understanding of content, as well as the development and progress of research.